ICI House, East Melbourne, 1958-1959 - Sievers, Wolfgang, 1913-2007. (1958)
Illustrates the architecture and interior design of the ICI House in Melbourne, Victoria by architects Bates Smart amd McCutcheon.
1,4. ICI House, East Melbourne. Exterior, 1959 --2,3. ICI House, East Melbourne. Exterior during construction, 1958 -- 5,6,9. ICI House, East Melbourne. Entrance, 1959 -- 7. ICI House, East Melbourne. Foyer, 1959 -- 8. ICI House, East Melbourne. Foyer showing stairs, 1959. -- 10. ICI House, East Melbourne. Exterior at night, 1958 --11,19. ICI House, East Melbourne. Office interior with typists, 1958 -- 12. ICI House, East Melbourne. Cafeteria showing planter -- 13,20. ICI House, East Melbourne. Cafeteria, 1959 -- 14. ICI House, East Melbourne. Garage, 1959. -- 15. ICI House, East Melbourne. Executive office, 1959 -- 16. ICI House, East Melbourne. Executive dining room, 1959 -- 17. ICI House, East Melbourne. Lecture theatre, 1959 -- 18. ICI House, East Melbourne. Telephone switchboard, 1958.
Title from accession record.
This set of 20 photographs is part of a collection of 500 photographs by Wolfgang Sievers on Australian architecture and interior design from 1949 to 1976.
Captions, dates of printing and negative numbers verso.
Images individually catalogued and digitised.
Also available online
List available.
Keywords: Sievers, Wolfgang, -- 1913-2007 -- Photograph collections; ICI House (Melbourne, Vic.) -- Photographs; Bates, Smart and McCutcheon; Architectural photography -- Victoria -- Melbourne; Buildings -- Victoria -- Melbourne -- Photographs